Consumer perspective of omnichannel commerce - Kaczorowska-Spychalska Dominika (Management)
The evolution of hypermedia space and growing saturation of the market with mobile devices, an increasing role of Big Data, which allow for multidimensional analysis of data from offline and online markets, growing popularization of solutions of Market Intelligence supported by Cloud Computing technology as well as development of potential and opportunities of adapting the Artificial Intelligence (AI) and Internet of Things (IoT) in commerce cause that customers and their experience become a major point of activity of companies/brands. Shopping experience of a buyer is an effect of multiple and multidimensional contacts, often conducted simultaneously in many channels and in the real time. It forces an increasingly growing number of challenges that companies/brands are presented with if they want to optimize a space of customer journey and have to ensure continuity, coherence and complexity of experiences for their customers. Searching or creating these benefits that customers expect and their constant development becomes a prerequisite in this situation so that variety of positive experiences resulting in customer satisfaction and happiness could be guaranteed.